Mental health issues is common, resiliency is rare: Qataris and residents' experiences with distress, traumatic symptoms, and coping during the blockade. - Wahiba Abu-Ras; Maryam Burghul; Eliza Decker (Public Library of Science (PLoS), 2023)
Many people feel vulnerable and uncertain about their future during a political crisis or political instability. Nonetheless, people may choose different coping strategies, making some more resilient and others more vulnerable to mental health issues. Added to the stress caused by these political factors is that social media has become the only source of information, including intolerance, hate speech, and bigotry. Therefore, reactive strategies to traumatic events and resiliency are essential components in addressing the affected population's stress and mental health issues. Although much attention has been paid to the political blockade imposed on Qatar in 2017, little emphasis has been placed on its impact on the affected people's mental health, coping strategies, and resiliency. The study explores Qatari citizens' mental health, resilience, distress, traumatic symptoms, and coping in the context of the blockade. This study fills the knowledge gap in this area by using a mixed-method approach with 443 online surveys and 23 face-to-face interviews. Quantitative data shows women scored higher on distress than men (17.37 v 9.13, p = .009), but men scored higher on resiliency (73.63 v 68.19, p = .009). Qualitative data supported these findings. The findings will lay the foundation for clinical trials and social interventions to provide better mental health services to Qatari families directly affected by the blockade and inform mental health providers and policymakers about stress, coping strategies, and resilience during this crisis.